Clima organizacional de las unidades administrativas, de la Universidad Estatal de Bolívar, periodo 2024 – 2028. - Azas Rea Jefferson Vinicio (2025)
This research addresses the organizational climate in the Administrative Units of the Universidad Estatal de Bolívar during the 2024-2028 period. The organizational climate directly influences the motivation, satisfaction, and productivity of employees, being essential for institutional success. The objective is to determine how the organizational climate influences job satisfaction among employees of the Administrative Units of the Universidad Estatal de Bolívar. A qualitative and quantitative approach was used, applying surveys and direct observations to 93 employees. Techniques included questionnaires to evaluate dimensions of the organizational climate and observation sheets to record interactions and behaviors in the workplace. The analysis revealed that a high percentage of employees (89.2%) are familiar with the organizational climate, and the majority (73.1%) considers that the university effectively complies with labor laws. However, 35.5% perceive motivation as regular, and 26.9% do not receive regular feedback on their performance. Communication also showed areas for improvement, with 29.1% rating it as regular or poor. Infrastructure and resources were adequate, but the need to improve incentive and recognition programs was identified. The research highlights the importance of implementing strategies to improve motivation, communication, and feedback in the Administrative Units. Improving these areas could increase job satisfaction, reduce staff turnover, and optimize the university's operational efficiency. It is recommended to design a strategic plan to address these challenges and promote a more positive work environment. Keywords: Organizational climate, job satisfaction, communication, motivation, feedback.